The Role of Audit Quality in Moderating the Effect of Corporate Social Responsibility and Capital Structure on Financial Distress - Indriana Titerlie; Michael Christian (Indonesian Interdisciplinary Journal of Sharia Economics)
This study investigates the impact of corporate social responsibility and capital structure on financial distress, as well as the moderating influence of audit quality, within transportation and logistics firms listed on the Indonesia Stock Exchange from 2021 to 2023. Data from 102 firm-year observations across 34 organizations were examined employing multiple linear regression and moderation analysis via SPSS version 26. The findings demonstrate that corporate social responsibility (CSR) has a negative but insignificant effect on financial distress, suggesting that CSR activities have not yet contributed meaningfully to financial stability. Conversely, capital structure exerts a substantial negative impact, suggesting that proficient management aids in alleviating the danger of financial distress. Audit quality does not moderate the relationship between CSR and financial distress but it greatly diminishes the impact of capital structure. This outcome indicates that while a robust capital structure might mitigate financial distress, high-quality audits may uncover latent risks, potentially undermining the apparent efficacy of financing options. The results underscore the necessity of integrating CSR with financial risk management and the relevance of meticulously evaluating the influence of audit quality on financial reporting.